Using monomorphic microsatellite markers in oil palm (Elaeisguineensis Jacq.) - Hama-Ali, Emad Omer; Tan, Soon Guan (Shastri Education Trust, 2014)
Molecular markers in oil palm characterization and breeding began two decades ago. Microsatellite markers are a system that is commonly used in oil palm research since its development. Monomorphic SSR markers have been eliminated from all evolutionary and population genetics studies by researchers because of their lack of genetic variability. The goals of this study were to review polymorphic DNA microsatellite marker system also known as simple sequence repeats(SSR) in oil palm research since its development and to employa monomorphic SSR marker for detection of illegitimacy in oil palm breeding programs. Ten monomorphic SSR markers and two half-sib families were used in this study. Illegitimate offspring IDs 97 and 180 were found by four monomorphic locimEgCIR0425, mEgCIR3477, mEgCIR3769, and mEgCIR3902 in Family-1and Family-2. In addition, five loci (mEgCIR3574, mEgCIR3607, mEgCIR3672, mEgCIR3785 and mEgCIR3807) detect one illegitimate offspring ID 180.This study showed that monomorphic SSR markers are suitable for the detection of illegitimate offsprings in oil palm breeding programs.